2012
DOI: 10.1007/s00442-012-2479-5
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial protease inhibitors lead to maternal transfer of increased protease gene expression in Daphnia

Abstract: Protease inhibitors (PIs) have frequently been found in cyanobacterial blooms and have been shown to affect the major herbivore Daphnia by decreasing growth and inhibiting gut protease activity. However, it has been shown that a clone of Daphnia is able to respond to dietary PIs by increasing its protease gene expression. Such an inducible response might be maternally transferred to the next generation. Therefore, we tested a tolerant clone for maternal transfer of protease gene expression. When exposed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 55 publications
0
28
1
Order By: Relevance
“…Nevertheless, it has been shown that Daphnia are able to respond to such inhibitors by an increase in protease gene expression (Schwarzenberger et al, ). This increased protease gene expression was demonstrated to be maternally transferred to the offspring of pre‐exposed mothers, which causes higher somatic growth rates of their offspring in comparison to offspring from naïve mothers (Schwarzenberger & Von Elert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been shown that Daphnia are able to respond to such inhibitors by an increase in protease gene expression (Schwarzenberger et al, ). This increased protease gene expression was demonstrated to be maternally transferred to the offspring of pre‐exposed mothers, which causes higher somatic growth rates of their offspring in comparison to offspring from naïve mothers (Schwarzenberger & Von Elert, ).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas adaptations to natural environments have been demonstrated in ecologically relevant organisms, the genetic basis of adaptation has mainly been investigated in genetic model organisms whose adaptations to environmental variability are of minor interest. In the case of Daphnia , studies identifying genes that account for adaptive traits are scarce, and are based on qPCR analyses of candidate genes which were identified on the basis of a-priori knowledge of their function [35, 36]. By using a transcriptome-wide approach, we have been able to answer the question as to which genes are involved in microcystin tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Increased cyanobacterial densities can act as an important selection agent on zooplankton populations since cyanobacteria produce harmful compounds [9]. In the context of exposure to toxic cyanobacteria, daphniids either induce resistance within a life-time and pass it on to following generations [1619], or evolve rapidly resistance over multiple generations [2023]. Rapid evolution of organisms in response to environmental changes usually stem from selection on pre-existing genetic variation because beneficial alleles are already available and their probabilities are often higher than de novo mutation [40].…”
Section: Discussionmentioning
confidence: 99%
“…A short-time exposure to toxic cyanobacteria induces zooplankton defenses and enhances their fitness in cyanobacterial conditions [1315]. These inducible defenses developed within one generation can be transferred to following generations via maternal effects and can contribute to neonatal success [1619]. In addition to physiological adaptations, zooplankton can rapidly evolve genetically based resistance to toxic cyanobacteria [2023].…”
Section: Introductionmentioning
confidence: 99%